Preserved ratio impaired spirometry, plasma proteomics, and incident heart failure - Geng, Yang; Ding, Yi; Pei, Yalong; Zhou, Xiya; Lu, Xujia; Xu, Mingcan; Borné, Yan; Ke, Chaofu (Journal of advanced research, 2025)
INTRODUCTION: Epidemiological evidence suggests the association of preserved ratio impaired spirometry (PRISm) at baseline with the risk of heart failure (HF), however, the associations between transitions of PRISm and incident HF remain to be clarified. Furthermore, the causal relationship and underlying biological mechanisms linking PRISm and HF are unclear. OBJECTIVES: This study aimed to investigate the association between the normal-PRISm transition and incident HF, and further evaluate the causal relationship and underlying molecular mechanisms linking PRISm and HF. METHODS: A total of 32,202 individuals with repeated spirometry and 40,047 individuals with proteomic data were included from the UK Biobank. Cox proportional hazards models were employed to estimate the association between the normal-PRISm transition and HF risk. Mendelian randomization (MR) analysis was performed to investigate the causal relationship between PRISm and HF. Mediation analysis was conducted to elucidate the mediation effects of 2,923 plasma proteins. RESULTS: Compared with consistent normal spirometry, the normal-PRISm transition was associated with an elevated risk of HF (hazard ratio: 1.814, 95% CI: 1.128, 2.919). The MR suggested a causal link between PRISm and HF (odds ratio: 1.488, 95% CI: 1.040, 2.130). In addition, 672 proteins demonstrated significant mediation effects, and the overall proteomic score mediated approximately 59.63% (95% CI: 46.98%, 77.12%) of the relationship between PRISm and HF. CONCLUSION: Individuals with the normal-PRISm transition were at an elevated risk of HF. The MR results suggested the causal link between PRISm and HF, and a variety of plasma proteins substantially mediated the relationship between PRISm and HF.
Copyright © 2025 The Author(s). Published by Elsevier B.V. All rights reserved.